PENGEMBANGAN MODUL AJAR UNTUK KURIKULUM BERBASIS MERDEKA BELAJAR DI PAUD SKB JAKARTA BARAT - Cecilia, Clarisa; Imelda, Elsa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Learning in PAUD SKB uses an independent curriculum so that education in PAUD is learning while playing. In this case, the type of activity chosen must be able to provide a fun and meaningful experience for students. SKB education also focuses on developing the personality of individual students, so that the development of each student is monitored from a cognitive and psychosocial perspective. Student creativity must also be encouraged from an early age so that it can develop properly as students grow (Intishar, 2003520). Therefore, in connection with the implementation and realization of the SKB PAUD independent curriculum, teaching modules were created to support the learning process in the classroom. Module is one of various types of teaching tools that contain lesson plans that guide the teaching process to achieve learning objectives. The purpose of developing teaching modules is to provide teaching materials that can guide educators in the implementation of learning in the classroom. The development of modules made as teaching materials in the PAUD SKB consists of 5 themes, namely Myself, My Family and Environment, My Needs, Animals and Plants. Each theme consists of several sub-themes which include learning objectives, theoretical basis, various creativity and student activity sheets related to the theme. This module is made by collecting from various sources such as the internet, books, as well as creativity and previous student worksheets. With teaching modules, it will be more helpful in the teaching and learning process in class, because the learning process will be more coordinated and interesting. This is because students can explore through various creativity and activity sheets provided. Therefore, the development of modules that are made can support the implementation of the Independent Curriculum at PAUD SKB, namely playing while learning. Pembelajaran pada Pendidikan Anak Usia Dini (PAUD) SKB menggunakan Kurikulum Merdeka sehingga pendidikan di PAUD bersifat belajar sambil bermain. Dalam hal ini, jenis kegiatan yang dipilih harus dapat memberikan pengalaman yang menyenangkan dan bermakna bagi siswa. Pendidikan di PAUD SKB juga menitikberatkan pada pengembangan kepribadian siswa secara individu, sehingga perkembangan setiap siswa terpantau dari sisi kognitif dan psikososial. Kreativitas siswa juga harus didorong sejak dini agar dapat berkembang dengan baik seiring pertumbuhan siswa (Intishar, 2020). Oleh karena itu, sehubungan dengan implementasi dan realisasi kurikulum merdeka PAUD SKB, maka dibuat modul ajar untuk menunjang proses pembelajaran di kelas. Modul adalah satu dari berbagai jenis alat ajar yang berisi rencana pembelajaran yang memandu proses pengajaran untuk mencapai tujuan pembelajaran. Tujuan pengembangan modul ajar adalah menyediakan bahan ajar yang dapat membimbing pendidik dalam pelaksanaan pembelajaran di kelas. Pengembangan modul yang dibuat sebagai bahan ajar di PAUD SKB terdiri dari 5 tema yaitu Diri Sendiri, Keluarga dan Lingkunganku, Kebutuhanku, Hewan, dan Tanaman. Tiap tema terdiri dari beberapa sub tema yang mencakup tujuan pembelajaran, landasan teori, berbagai kreativitas dan lembar aktivitas siswa yang berkaitan dengan tema. Modul ini dibuat dengan mengumpulkan dari berbagai sumber seperti internet, buku-buku, serta kreativitas dan lembar kerja siswa sebelumnya. Dengan adanya modul ajar, akan lebih membantu dalam proses belajar mengajar di kelas, karena proses pembelajaran akan lebih terkoordinasi dan menarik. Hal ini dikarenakan siswa-siswi dapat bereksplorasi melalui berbagai kreativitas dan lembar aktivitas yang disediakan. Oleh sebab itu, pengembangan modul yang dibuat dapat mendukung penerapan Kurikulum Merdeka di PAUD SKB, yaitu bermain sambil belajar.